MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA SISWA DENGAN PENERAPAN THE POWER OF TWO - Dina Oktarina (Departemen Matematika, 2018)
Understanding of mathematical concepts is a basic capabilities that must be improved in students. In fact, understanding of mathematical concepts in class VIII SMPN 18 Padang is still low. The solutions to resolve it by applying active learning model of The Power of Two. Type of research is quasy experiment with the static group design. Sample research is taken by simple random sampling. The result showsthat students’understanding of mathematical concepts by applying active learning model of The Power Of Twois better than students’understanding of mathematical conceptsby applyingconventional learning. It can be concluded that active learning model of The Power of Two gives positive influences towards to understanding of mathematical concepts.Keywords – conventional learning,mathematical concepts, the power of two